NILAI-NILAI PENDIDIKAN TASAWUF AKHLAQI (STUDI ANALISIS PEMIKIRAN RKH. MUHAMMAD SYAMSUL ARIFIN DALAM BUKU KALAM HIKMAH) - Hosen; Abdul Mukit; Faisal Amir (STAI Al-Hamidiyah Bangkalan, 2021)
Tasawuf Akhlaqi is teaching that discusses the perfection and purity of the soul, which is formulated in strict regulation of mental attitudes and behavior discipline, in order to achieve perfect and optimal happiness. So, we need purification efforts in humans through the cultivation of Sufism values. The book Kalam Hikmah is a small book that explains the values of Sufism education but focuses more on the values of Islamic Sufism. RKH writes this book. Muhammad Syamsul Arifin, in which there are Sufism values that are part of Islamic Sufism values. This research is a literature review, which is done by reading, reviewing or examining library materials. The primary data source is the book Kalam Hikmah written by RKH. Muhammad Syamsul Arifin and his secondary sources in the form of books or other documents support and relate to Kalam Hikmah's book. Meanwhile, data analysis techniques use content analysis. Educational values, Islamic Sufism. The results showed that: 1) The values of the Islamic Tasawuf Education contained in the Kalam Hikmah Book by RKH. Muhammad Syamsul Arifin includes Istiqomah, Sabar, Tawadhu ', Wara', Qona'ah and Tawakkal, 2) Typology of Islamic Thought by RKH Muhammad Syamsul Arifin, in the book of Kalam Hikmah is a Typology of Traditional Islamic Thought because it emphasizes Islamic thought, which is still firmly tied to the ulama thinkers 'experts in fiqh, hadith, tasawuf. The lives of scholars' who lived between the 7th century AD Until the 13th century AD, 3)